Perceived Impact of a Land and Property Rights Program on Violence Against Women in Rural Kenya: A Qualitative Investigation. (December 2016) - Hilliard, Starr; Bukusi, Elizabeth; Grabe, Shelly; Lu, Tiffany; Hatcher, Abigail M.; Kwena, Zachary; Mwaura-Muiru, Esther; Dworkin, Shari L.
The current study focuses on a community-led land and property rights program in two rural provinces in western Kenya. The program was designed to respond to women's property rights violations to reduce violence against women and HIV risks at the community level. Through in-depth interviews with 30 women, we examine the perceived impact that this community-level property rights program had on violence against women at the individual and community level. We also examine perceptions as to how reductions in violence were achieved. Finally, we consider how our findings may aid researchers in the design of structural violence-prevention strategies.